TRANSFORMATION ON THE MUSLIM WOMEN ROLE AND ITS IMPACT ON THE FAMILY RESILIENCE - Suripto, Agus Suryo; Rofiq, Ahmad; Jamil, Muhsin (Indonesian Journal of Islamic Literature and Muslim Society, 2020)
Transformation on the women role can be considered as the process of developing the mankind civilization. In the past, the transformation of women had been more by the economic motive. Along with the turn of the century, the women roleÂ hasÂ not only been dominated by the economy-related motive and domain but has expanded to the domains that used to be occupied by men. As a result, such role transformation has brought certain impacts to the actors. With reference to the statement, the high figure of divorce law suit has been suspected as one of the impacts caused by the transformation. Therefore, through the review several efforts will be pursued in order to identify why, on the one hand, women have crippled the family resilience and, on the other hand, women have strengthened the family resilience. The results of the review show that the transformation on the women role have resulted in two different conditions within the family resilience. The vulnerability and the strength of the family resilience might at least be categorized into three dimensions namely the dimension of physical resilience, the dimension of social resilience, and the dimension of psychological resilience. In terms of physical resilience, both the vulnerable family and the strong family have relatively met their fundamental needs. On the contrary, there are differences in the other two dimensions namely the social resilience and the psychological resilience. In terms of social resilience, the vulnerable family and the strong family has displayed different quality on the aspects of conflict management, effective communication, and religious values. Similarly, in terms of psychological resilience the vulnerable family and the strong family has also displayed different quality on the aspects of positive self-concept, right and responsibility fulfilment satisfaction, family harmony maintenance, mutual respect and self-esteem, and compassion. The different quality on the dimension of social resilience and the dimension of psychological quality has resulted in the different end of the family life.